Tuberculosis-associated respiratory impairment and disability in children, adolescents and adults: protocol for a systematic review and individual participant data meta-analysis - Andrea Benedetti; Dick Menzies; Kamila Romanowski; Faiz Ahmad Khan; Mayara Lisboa Bastos; Silvia S. Chiang; James C. Johnston; Alexandre Petiquan; Sierra A. Land; Marieke M. van der Zalm; Jonathon R. Campbell (BMJ Open)
Background Approximately 2% of the global population has survived tuberculosis (TB). Increasing evidence indicates that a significant proportion of pulmonary TB survivors develop TB-associated respiratory impairment and disability—commonly referred to as post-TB lung disease—marked by impaired respiratory function, persistent symptoms and activity limitations. However, the prevalence, risk factors and progression of TB-associated respiratory disability throughout the life course are not well understood. To address these gaps, we will undertake a systematic review and individual participant-level data meta-analysis (IPD-MA) focusing on TB-associated respiratory impairment and disability in children, adolescents and adults successfully treated for pulmonary TB.Methods and analysis We will systematically search MEDLINE, Embase, CENTRAL, Global Index Medicus and medRxiv for original studies investigating TB-associated respiratory impairment and disability in people of all ages who have completed treatment for microbiologically confirmed or clinically diagnosed pulmonary TB. Authors of eligible studies will be invited to contribute deidentified data and form a collaborative group. Primary outcomes will be (1) abnormal lung function based on spirometry parameters and (2) chronic respiratory symptoms. We will estimate the overall and subgroup-specific prevalence of each outcome through IPD-MA. Next, we will develop clinical prediction tools assessing the risk of future TB-associated respiratory impairment and disability. Finally, we will use stepwise hierarchical modelling to identify epidemiological determinants of respiratory impairment and disability.Ethics and dissemination This study has been approved by the ethics review boards at the Rhode Island Hospital (2138217-2) and the Research Institute of the McGill University Health Centre (2024-10345). Individual study authors will be required to obtain institutional approval prior to sharing data. Results will be disseminated through open-access, peer-reviewed publications and conference presentations.PROSPERO registration number CRD42024529906.